Adenosine deaminase level in the serum of the patients Toxoplasma gondii seropositive and Giardia intestinalis - Karaman, Uelkue; Beytur, Leyla; Kiran, Tugba Raika; Colak, Cemil (Academic Journals, 2009)
Adenosine deaminase (ADA) is an aminohydrolase making adenosine, deoksiadenozini inozin, and deocsiniozine deaminise irreversibly and plays role in the catabolism of purine nucleotids. Toxoplasma gondii is a zoonoses intracellular parasite that causes infection in animals and humans. This parasite encompasses enzymes that produce free radicals such as superoxide and hydrogen peroxide. In addition, Giardia intestinalis is another parasite that causes irritations in mucosa, over mucus discharge, aggravating former inflammations, and various absorption defects. In the present study, it has been aimed to compare ADA levels between T. gondii seropositive (IgG seropositive but symptomless patients), G. intestinalis positive patients, and control group. Thus, ADA levels between 32 patients being T. gondii seropositive and 29 controls and between 50 patients' G. intestinalis positive and 40 controls have been evaluated. The results were analyzed using independent samples t-test at the level of p < 0.05. According to this, in the statistical comparison between the parameters of patient and control groups, a meaningful decrease could be determined in ADA levels. This situation can be commented in the way that toxoplasmosis infection being inactive does not necessarily cause an increase in T lymphocytes. In addition, this decrease can be due to increasing oxidative stress in parasitic infections.
Keywords: Toxoplasma gondii; Giardia intestinalis; adenosine deaminase